Wound-inducible ANAC071 and ANAC096 transcription factors promote cambial cell formation in incised Arabidopsis flowering stems - Keita Matsuoka (Nature Portfolio, 2021)
Matsuoka et al. study the mechanism by which transcription factors ANAC071 and ANAC096 promotes regeneration of wounded tissue in Arabidopsis by mutagenesis and morphological characterization. They find that these factors are essential for wound-induced cambium formation from dedifferentiated cells before the initiation of cell division.